Analysis of Feminist Principels in The Da’wah Agenda of Gender Equality - Karimuddin Nasution; Mohd Faizulamri Mohd Saad (UIR Press, 2020)
One of the da’wah that is quite intense this time in the media is the da'wah feminist group for gender equality. The main mission of Muslim feminists is to equalize men and women in all matters. To fulfill this mission, they always lay down the basic principles of gender equality taken from the Koran and the hadith, then they will interpret textually. Only after that was reached did they interpret the Koran and the Hadith in accordance with their wishes. If it contradicts the verses that place men and women differently they will usually deny it on the grounds that it conflicts with the principle of gender equality. This study aims to analyze the principles of gender equality in the gender equality da’wah agenda. Methodology of this study was qualitative using document analysis. Data collection was done through library research. The data were analyzed using descriptive, comparative and critique. The findings showed that the feminists made Qur’anic verses as the principles of gender equality. The principles are men and women alike servants, men and women alike caliphs, men and women alike accept the covenant when they are in the womb, Adam and Eve are both engaged in transgression in heaven until had been sent to the earth, men and women equally have potential in every aspect of life. The Qur’anic verses that are made as the basis of the principles of gender equality seem to be over-implemented. The tafsir scholars do not explain the verses in the context of male and female relationships. The implication of this study is that Muslims are encouraged to refer to the interpretation of the authority scholars who have been recognized by the Muslim’s world, therefore is no mistakes in understanding the verses of the Qur’an. It is also expected to give a real understanding of the relationship between men and women in the Qur’an